2017
DOI: 10.1097/fch.0000000000000072
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Exposure Therapy

Abstract: Pregnant and parenting adolescents often experience high rates of intimate partner violence (IPV) and its sequelae posttraumatic stress disorder (PTSD) and depression. Narrative Exposure Therapy (NET) is an innovative intervention that has demonstrated strong preliminary evidence in improving mental health. The specific aims of this article are threefold: a) provide a brief background about IPV-related PTSD and depression among pregnant and parenting adolescents, b) describe NET’s theoretical principals, its t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 98 publications
(197 reference statements)
1
12
0
Order By: Relevance
“…There is a significant need to determine the efficacy and effectiveness of both exposure-based treatments and those that do not involve providing a detailed trauma account. Thus, exposure-based therapies, such as PE, NET, and TF-CBT, are promising approaches to systematically explore in future research alongside other evidence-based treatments, such as CPT (National Institute for Health and Clinical Excellence, 2014;Volpe, Quinn, Resch, Douglas, et al, 2017;Volpe, Quinn, Resch, Sommers, et al, 2017). For pregnant women with subthreshold PTSD symptoms or women who prefer not to engage in trauma-focused treatment, interventions such as SMC and SS may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a significant need to determine the efficacy and effectiveness of both exposure-based treatments and those that do not involve providing a detailed trauma account. Thus, exposure-based therapies, such as PE, NET, and TF-CBT, are promising approaches to systematically explore in future research alongside other evidence-based treatments, such as CPT (National Institute for Health and Clinical Excellence, 2014;Volpe, Quinn, Resch, Douglas, et al, 2017;Volpe, Quinn, Resch, Sommers, et al, 2017). For pregnant women with subthreshold PTSD symptoms or women who prefer not to engage in trauma-focused treatment, interventions such as SMC and SS may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological interventions and treatments for PTSD are likely acceptable and feasible during pregnancy, as suggested by the studies reviewed herein. Moreover, prior research has demonstrated that integrated approaches within medical settings as well as community-based approaches may be effective, cost-saving, and could potentially minimize mental health stigma (Arch et al, 2012;Malebranche et al, 2017;Volpe, Quinn, Resch, Sommers, et al, 2017). Further, technology-based approaches should also be considered given treatment barriers both preceding and exacerbated by the COVID-19 pandemic (Torous & Wykes, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conceptual diagram of how women in Afghanistan safe houses describe the therapeutic effects of storytelling largely contradicts biomedical understandings of how individuals recover from trauma through telling personal narratives. Whereas cognitive behavioural therapy (CBT) and exposure therapies (PE and NET) focus on the telling and retelling of a specific traumatic event as a means of alleviating symptoms of trauma (Volpe et al, 2017), our results highlighted the presence of multiple traumatic events and a need for participants to discuss these traumas in the context of narratives that reaffirm positive self-identities in the face of persistent patriarchal and structural gender violence. Doing so presents a major challenge to biomedical approaches to M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT trauma focused on 'maladaptive' cognitions by highlighting the social, rather than individual, nature of the trauma and its related symptoms.…”
Section: Discussionmentioning
confidence: 83%
“…With a follow-up period of less than a month, NET was found to be more effective in reducing negative emotions associated with change but not in reducing feelings of stigma or increasing social support. One study found that when NET was used for the successful treatment of serious illnesses, it could also help people feel better emotionally [ 49 ]. However, the strength of the data was deemed insufficient to assess the effect of story exposure treatment on patients with negative emotions since only 3 of the 12 studies investigated social support [ 33 - 35 ].…”
Section: Discussionmentioning
confidence: 99%